The Relationship of Knowledge About Radiation Hazard Risk with The Level of Compliance with PPE Use in Workers in The Radiology Department of Hospitals - Nurmalia Nurmalia; Indriyani Indriyani; Rindi Amelia (Sriwijaya Journal of Medicine, 2022)
The use of nuclear technology is increasingly high in various aspects, one of which is medicine, especially in the radiology section. X-rays have a very high penetrating power against the material they pass. So that X-rays can be used as a diagnostic and therapeutic tool in medicine. However, the risk of possible harm to radiation workers is that it can cause hematopoietic damage (blood disorders), such as anemia, leukemia, and leukopenia. Therefore, radiation protection and safety measures are indispensable. Knowledge of the risk of radiation hazards is one of the things that can prevent the impact of radiation. Objective: This study aims to determine the relationship between Radiation Hazard Risk Knowledge and the Level of Compliance with the Use of PPE for Radiation Workers in the Radiology Section of Hospitals in Palembang. Method: This study is an observational analytical, quantitative research design using a cross-sectional approach on 25 respondents’ radiation workers in the radiology department of RSUP Rivai Abdullah, and RSUD Palembang Bari were taken using total sampling. The instrument uses questionnaires on the level of knowledge of radiation hazards and the level of compliance. Results: Fisher's analysis obtained a value of p = 1000, meaning there is no relationship between knowledge and compliance. Conclusion: The results of this study show no relationship between radiation hazard risk knowledge and the level of compliance with the use of PPE for radiation workers in the radiology department of hospitals in Palembang.